Evaluasi Reaksi Obat Merugikan pada Pasien Kemoterapi Kanker Payudara di Salah Satu Rumah Sakit di Bandung - ELIN YULINAH SUKANDAR; SRI HARTINI; PUTRI RIZKITA (Fakultas Farmasi Universitas Pancasila, 2014)
Chemotherapy is one of the breast cancer treatments. However, there are several adverse effects with mild to high severity related to this treatment. This study was made to evaluate adverse effects which occurred in breast cancer patients who are still in their chemotherapy cycle. The evaluation consists of assessment of adverse effects associated with chemotherapy regimens and its dosage, causality assessment, and preventability assessment. This study was done from December 2012 until March 2013 concurrently. The data was collected directly from the patients by doing the interview. The data was also collected from the patient’s medical record and nurse’s daily documentation. Clinically, FAC caused more adverse effects than other chemotherapy regimens. However, in the 6% of excess dosage, there were no different acute adverse effects. The most occurred adverse effect was alopecia with 81% percentage. Causality assessment with probability scale Naranjo and WHO criteria showed that 97.3% and 99.2% were ‘probable’. The preventability assessment which based on Thornton- Schumock criteria showed that only nausea and vomit which were ‘definitely preventable’.